Positive Cumulative Fluid Balance Is Associated With Mortality in Pediatric Acute Respiratory Distress Syndrome in the Setting of Acute Kidney Injury. Issue 4 (April 2019) - Zinter, Matt S.; Spicer, Aaron C.; Liu, Kathleen D.; Orwoll, Benjamin E.; Alkhouli, Mustafa F.; Brakeman, Paul R.; Calfee, Carolyn S.; Matthay, Michael A.; Sapru, Anil
Abstract : Objectives: As acute kidney injury and elevated cumulative fluid balance commonly co-occur in pediatric acute respiratory distress syndrome, we aimed to identify risk factors for their development and evaluate their independent relationships with mortality. We hypothesized that acute kidney injury and elevated cumulative fluid balance would be associated with markers of inflammation and that children with elevated cumulative fluid balance and concomitant acute kidney injury would have worse outcomes than other children. Design: Prospective observational study using the pediatric Risk, Injury, Failure, Loss, End-Stage acute kidney injury classification. Setting: Five academic PICUs. Patients: Two-hundred sixty patients 1 month to 18 years old meeting the Berlin definition of acute respiratory distress syndrome between 2008 and 2014. Interventions: None. Measurements and Results: PICU mortality was 13% (34/260). Relative to survivors, nonsurvivors had greater cumulative fluid balance on day 3 of acute respiratory distress syndrome (+90.1 mL/kg; interquartile range 26.6–161.7 vs +44.9 mL/kg; interquartile range 10.0–111.3; p = 0.008) and also had higher prevalence of acute kidney injury on day 3 of acute respiratory distress syndrome (50% vs 23%; p = 0.001). On stratified analysis, greater cumulative fluid balance on day 3 of acute respiratory distress syndrome was associated with mortality among patients with concomitant acute kidney injury (+111.5 mL/kg for nonsurvivors; interquartile range 82.6–236.8 vs +58.5 mL/kg for survivors; interquartile range 0.9–176.2; p = 0.041) but not among patients without acute kidney injury ( p = 0.308). The presence of acute kidney injury on acute respiratory distress syndrome day 3 was associated with mortality among patients with positive cumulative fluid balance (29.1% vs 10.4% mortality; p = 0.001) but not among patients with even or negative cumulative fluid balance ( p = 0.430). Day 1 plasma interleukin-6 levels were associated with the development of day 3 positive cumulative fluid balance, day 3 acute kidney injury, and PICU mortality and the association between elevated day 1 interleukin-6 and PICU mortality was partially mediated by the interval development of day 3 positive cumulative fluid balance and day 3 acute kidney injury ( p < 0.001). Conclusions: In pediatric acute respiratory distress syndrome, elevated cumulative fluid balance on day 3 of acute respiratory distress syndrome is associated with mortality specifically in patients with concomitant acute kidney injury. Plasma interleukin-6 levels are associated with the development of positive cumulative fluid balance and acute kidney injury, suggesting a potential mechanism by which inflammation might predispose to mortality. Abstract : Supplemental Digital Content is available in the text.